2010
DOI: 10.1021/ja101292a
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Acyl Substitution via Aromatic Cation Activation of Carboxylic Acids: Rapid Generation of Acid Chlorides under Mild Conditions

Abstract: The first example of aromatic cation-activated nucleophilic acyl substitution has been achieved. The conversion of carboxylic acids to their corresponding acid chlorides occurs rapidly in the presence of 3,3-dichlorocyclopropenes via the intermediacy of cyclopropenium carboxylate complexes. The effect of cyclopropene substituents on the rate of conversion is examined. The addition of tertiary amine base is found to dramatically accelerate reaction, and conditions were developed for the preparation of acid sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 16 publications
0
54
0
3
Order By: Relevance
“…On the basis of these findings, we have initiated a program aiming to use the safe and readily available difluorocarbene reagents for deoxyfluorination by virtue of 3,3-difluorocyclopropenes. This research program was inspired by Lambert's deoxychlorination with 3,3-dichlorocyclopropenes, which utilizes aromatic cyclopropenium cations as the activator for the transformation of monoalcohols and carboxylic acids to alkyl chlorides and acyl chlorides, respectively333438. We envisioned that under similar conditions, 3,3-difluorocyclopropenes may be used for deoxyfluorination of alcohols via nucleophilic attack of the alkoxycyclopropenium cation intermediate by the in situ -generated fluoride ion (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these findings, we have initiated a program aiming to use the safe and readily available difluorocarbene reagents for deoxyfluorination by virtue of 3,3-difluorocyclopropenes. This research program was inspired by Lambert's deoxychlorination with 3,3-dichlorocyclopropenes, which utilizes aromatic cyclopropenium cations as the activator for the transformation of monoalcohols and carboxylic acids to alkyl chlorides and acyl chlorides, respectively333438. We envisioned that under similar conditions, 3,3-difluorocyclopropenes may be used for deoxyfluorination of alcohols via nucleophilic attack of the alkoxycyclopropenium cation intermediate by the in situ -generated fluoride ion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After numerous trials and failures, we found that, unlike dichlorocyclopropenes333438, CpFluor 1a was only effective for the dehydroxyfluorination of carboxylic acids and benzyl alcohols39, and its fluorination of non-activated alcohols such as 3-phenylpropan-1-ol ( 2a ) was unexpectedly difficult. Table 1 shows the representative conditions that were screened with 2a as the model substrate.…”
Section: Resultsmentioning
confidence: 99%
“…56 Interestingly, recent attempts with the use of 3,3-dichloro-1,2-dimesitylcyclopropene 10 as a chlorination reagent in presence of DIEA as the base is quite promising with encouraging prospects. 55 Recently, the reagent is used for the conversion of carboxylic acids to their acid azides, which are later converted into ureidopeptides through Curtius rearrangement. 74…”
Section: Chlorinating Reagentsmentioning
confidence: 99%
“…Hardee et al developed an efficient aromatic cation activation method for rapid generation of acid chlorides in the presence of an amine (Scheme 25) 55. The protocol was mild enough to accommodate substrates with acid-sensitive functionalities such as glycol acetal, silyl ether, etc.…”
mentioning
confidence: 99%
“…Thus, they easily combine with an anion or a Lewis basic heteroatom leading to the reversible generation of the corresponding neutral carbocyclic species (Scheme 1). Owing to their unique reactivity, cyclopropenium ions, especially 2,3-diarylcyclopropenium ions, have been strategically exploited for the activation of the hydroxyl group of alcohols, carboxylic acids, oximes, and diols in various synthetically useful dehydrative processes to afford alkyl chlorides, 2,3 acid chlorides, 4 amides/lactams, 5,6 and cyclic ethers, respectively. 7…”
Section: Introductionmentioning
confidence: 99%